2018
DOI: 10.3390/en11081937
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fast Charging Efficiency under Extreme Temperatures

Abstract: Multi-type fast charging stations are being deployed over Europe as electric vehicle adoption becomes more popular. The growth of an electrical charging infrastructure in different countries poses different challenges related to its installation. One of these challenges is related to weather conditions that are extremely heterogeneous due to different latitudes, in which fast charging stations are located and whose impact on the charging performance is often neglected or unknown. The present study focused on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 7 publications
0
29
0
2
Order By: Relevance
“…A 22-36% decrease in the fast charge power at 0°C vs 25 °C has been found for Taxis in New York City [18], and the effect will be even larger at temperatures below 0°C [21]. Trentadu et al [21] found that the fast charge power for a specific BEV model was reduced to 4.1-4.8 kW at −25 °C and 4.3-17.6 kW at −15 °C, for different fast chargers tested in a laboratory environment when starting from 25% vehicle SOC. Above 25 °C the charge power was stable at the maximum achieved value of 38 and 47 kW depending on the charger they tested.…”
Section: Literature Reviewmentioning
confidence: 92%
See 2 more Smart Citations
“…A 22-36% decrease in the fast charge power at 0°C vs 25 °C has been found for Taxis in New York City [18], and the effect will be even larger at temperatures below 0°C [21]. Trentadu et al [21] found that the fast charge power for a specific BEV model was reduced to 4.1-4.8 kW at −25 °C and 4.3-17.6 kW at −15 °C, for different fast chargers tested in a laboratory environment when starting from 25% vehicle SOC. Above 25 °C the charge power was stable at the maximum achieved value of 38 and 47 kW depending on the charger they tested.…”
Section: Literature Reviewmentioning
confidence: 92%
“…The research on fast chargers have mainly focused on the technical design of the vehicle and the integration with and interface to the electricity network [8,9], the needs of users [6,[10][11][12], the optimum positioning and number of chargers needed to support the flow of vehicle [6,10,[13][14][15], cold/warm weather effects [16][17][18][19][20][21], and the use of fast chargers [6,10,11]. Few have however analyzed in depth the actual usage of fast chargers at a national scale for longer time periods, based on datasets from the fast charge operators.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Five DC fast charging columns, available on the market, were tested inside the Interoperability Laboratory of the Joint Research Center (Ispra, Italy). The chargers were equipped with combined charging system and CHAdeMO charging options and they were connected to the JRC electricity grid providing 400 V AC by means of a max 125 A, 50 Hz wall socket [Trentadue et al, 2018]. Table 1 describes the main technical specifications of the devices under test.…”
Section: Methodsmentioning
confidence: 99%
“…The main obstacle to the commercialization of electric vehicles (EVs)-environmentally friendly cars-is that they offer lower mileage for a single charge when compared with the mileage of internal combustion engines [1][2][3][4]. For vehicles with internal combustion engines, the vehicle cooling operation reduces fuel consumption by 20-30%, thereby reducing the mileage by 2%-30%; on the other hand, in the case of heating, fuel consumption is not affected as the waste heat of the engine is used [5][6][7].…”
Section: Introductionmentioning
confidence: 99%